Meningeal Melanocytes in the Mouse: Distribution and Dependence on Mitf - Gudjohnsen, Stefán A. H.; Atacho, Diahann A. M.; Gesbert, Franck; Raposo, Graca; Hurbain, Ilse; Larue, Lionel; Steingrimsson, Eirikur; Petersen, Petur Henry (Frontiers in Neuroanatomy, 2015)
Summary: Melanocytes are pigment producing cells derived from the neural crest. They are primarily found in the skin and hair follicles, but can also be found in other tissues including the eye, ear and heart. Here, we describe the distribution of pigmented cells in C57BL/6J mouse meninges, the membranes that envelope the brain. These cells contain melanosomes of all four stages of development and they depend on Microphthalmia associated transcription factor (MITF), the master regulator of melanocyte development, suggesting that they are bona-fide melanocytes. The location of these pigmented cells is consistent with the location of meningeal melanomas in humans and animal models. Significance: Here, we document and define pigmented cells in the meninges of the mouse brain and confirm that they are melanocytes. This is important for understanding the role of this cell type and for understanding primary meningeal melanoma, a rare disease that likely arises from normal meningeal melanocytes.